Representation of solutions of the Lamé–Navier system by endomorphisms on quaternions - Dinh, Doan Cong (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.54 Solutions of the Lamé–Navier system in R^3 are given in real analysis and in quatenionic analysis in different forms. We introduce a new method of using endomorphisms on quaternions with an aim to represent these solutions.